Proposed Framework for Professional Management to Syrian Construction Projects - ميا رنا (Latakia University Journal -Engineering Sciences Series, 2020)
Most developing countries have seen remarkable development in terms of setting up infrastructure, transportation, water installations, and industrial and telecommunications projects. It was noted the weakness of knowledge and tools of modern techniques related to the field of project management, especially the professional PMP, which caused the projects to fail to meet their requirements in terms of scope, cost and time. It has become necessary to think about project management systems to meet the qualitative and quantitative needs required, especially in the next stage of the reconstruction of Syria, with its multiple and overlapping projects, operations and goals, and thus the need for tools for planning and quantitative control of performance results. In the research, we studied the performance of construction projects and analyzed the factors affecting the implementation of construction projects in Syria according to the two basic aspects of managing the implementation of projects. The first included regulations and procedures for planning and control according to the knowledge areas of project management and the other addressed organizational behavior that relates to the organizational structure and management of individuals. The performance evaluation of the construction projects has shown deficiencies in several areas: the overall performance to achieve project goals, low human resource skills, and inadequate planning and control systems. Accordingly, a framework for the professional management of construction projects has been proposed that includes three strategic objectives and an organizational structure for the PMO for professional projects with specific projects and tasks to avoid identified shortcomings in project implementation in Syria.